68Ga-PSMA Uptake Patterns of Clear Cell Renal Carcinoma Across Different Histopathological Subtypes. (January 2022) - Oflas, Melis; Ozluk, Yasemin; Sanli, Oner; Ozkan, Zeynep Gozde; Kuyumcu, Serkan
Abstract : Abstract: 68 Ga–prostate-specific membrane antigen (PSMA) PET/CT is a well-established imaging modality in patients with prostate cancer; however, PSMA expression is also reported in the tumor-associated neovasculature, including but not limited to hepatocellular carcinoma, breast cancer, and renal cell carcinoma. Herein, we present 2 patients diagnosed with different histopathological subtypes of renal cell carcinoma who underwent 68 Ga-PSMA PET/CT before surgery. Both cases have different PSMA expression characteristics and are presented along with pathological findings.